(untitled) (Vietnam Journal of Community Medicine, 2026)
Objectives: To evaluate the early outcomes of posterior nasal nerve ablation for the treatment of chronic rhinitis in 108 Millitary hospital to improve symptoms and patient quality of life . Subjects and methods: A descriptive study was conducted on 30 patients diagnosed with chronic rhinitis whom is failed to control nasal symptoms by medical therapy or couldn’t treated by the medicine, treated at the 108 Millitarry Hospital from July to December 2025. Results: A total of 30 patients underwent treatment ( men/ women : 1,2/1), average age: 45± 10, youngest patient is 18 years old, oldest patient is 74 years old. Outcomes were assessed using SNOT-22 total score. Most patients showed noticeable changes before surgery and at the 3-month postoperative follow-up ( 53,3% did not require medical treatment, 40% showed a partial response, 6.7% experienced treatment failure)